Brazil: agricultural production and trade prospects - Tsigas, Eleni C (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The paper is organized as follows: section II presents trade patterns of the most important agricultural commodities for the last 15 years. Section III discusses the impact of changes in agricultural policies, and investment in infraestructure on agricultural production. Section IV discusses production and trade prospects for a number of agricultural commodities. Section V discusses several determinants of rural poverty and how it is linked with agrarian reform and land settlement in Brazil. Section VI summarizes the paper and it gives some policy recommendations.